Papillary Cystadenoma of the Epididymis - Yadav, Meghana; Agarwal, Deepti; Singh, Kulwant; Kundu, Parveen Rana; Hooda, Sunaina; Kaur, Swaran (Annals of Pathology and Laboratory Medicine, 2025)
Papillary cystadenoma of epididymis (PCE) is a benign neoplasm involving epididymis and frequently associated with Von Hippel-Lindau (VHL) disease. It is characterized by asymptomatic swelling, which is well circumscribed with papillary fronds on cut section. On microscopic examination, numerous cystic spaces with papillary infoldings are seen. These infoldings are covered with cuboidal to columnar epithelium. It is important to excise and do histopathological examination to rule out diagnosis of serous cystadenocarcinoma of paratestis, which mimic in symptomatology to papillary cystadenoma of epididymis but has poor prognosis. At the same time, regular ultrasonography done to rule out renal cell carcinoma as this entity is associated with VHL disease.